A generating function for generalized hypergeometric polynomial - Munot, P.; Padmanabham, P. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The object of the present paper is to establish a general expansion formula, which provides us a generating function for the generalized hypergeometric polynomials .